Receiving high-quality raw materials with improvement of drying process - Савченко-Перерва, Марина Юріївна; Радчук, Олег Володимирович; Гриньова, Дар’я Володимирівна; Болгова, Наталія Вікторівна (Technology audit and production reserves, 2015)
This article discusses the use of more effective and energy saving apparatus with counter-current swirling flows after the perfection in food, pharmaceutical, chemical, metallurgical and construction industries and gives the examples of some results of our research in this area. The main purpose of the research is to determine the optimal designs of dust collectors to increase the productivity of drying process. The use of the apparatus with counter-current swirling flows after the improvements in technological process of drying allows to increase the productivity of technological process, to improve the collection efficiency of the smallest fractions of the solid particles of milk, to reduce the hydraulic resistance of the apparatus and its geometrical dimensions. While analysing the obtained results with the use of different designs of dust collecting equipment the most optimum design for carrying out this technological process was determined. The research results can be applied by the process engineers involved in the field of food industry as well as construction, chemical, pharmaceutical and metallurgical ones. We propose to introduce more efficient energy-saving apparatus with counter-current swirling flows for the technological process of food drying.